Deciphering the genomic regions associated with seedling cold tolerance traits in rice (Oryza sativa L.) - Singh, Gurjeet; Pradhan, Anjan Kumar; Jyoti, Subroto Das; Harper, Chersty L.; Elumalai, Punniakotti; Sanchez, Darlene L.; Samonte, Stanley Omar PB; Talukder, Shyamal K. (Plant stress (Amsterdam), 2025)
•Seedling cold tolerance (SCT) is an important phenomenon for early planting and harvesting the second crop, as ratoon in many rice-growing regions in the world.•A total of 204 diverse rice germplasm accessions were screened for SCT-traits at the early seeding stage under natural cold, growth chamber, and controlled greenhouse conditions.•GWAS revealed 107 QTNs across the experiments, and six genetic markers showed pleiotropic responses for multiple SCT-traits in different experiments.•Identified potential candidate genes will be useful in understanding the genetic basis of SCT under cold stress and for the development of molecular markers for rice improvement. Seedling cold tolerance (SCT) in rice is important for planting rice in colder temperatures that occur during early planting and ratooning in some rice-growing regions in the world. Genome-wide association study (GWAS) has the potential to understand the genetic mechanisms of complex traits like SCT. A set of 204 rice accessions were screened for SCT traits in three environments: natural cold conditions (E1; temperature 6.3 °C-23.3 °C), growth chamber cold conditions (E2; 10 °C in 1st and 2nd weeks followed by 17 °C in 3rd and 4th weeks), and normal growth condition in the greenhouse (E3; day and night temperature maintained at 28–30 °C). Data collected on the number of emerged seedlings at six, eight, and twelve days after sowing, and seedling length (SL) was measured at two and four weeks after sowing. GWAS analysis identified nine quantitative trait nucleotides (QTNs) with phenotypic variation ranging from 10.98 to 20.72%. Among them, S06_22947376, S07_27594541, and S07_3833577 showed pleiotropic responses for multiple traits in different experiments. Candidate gene analysis of S06_22947376 identified four putative genes, i.e., Os06g0585950, Os06g0585982, Os06g0586150, and Os06g0587200 around the region to be associated with a protein kinase responsible for increasing the SCT. The results of this study provide valuable information for understanding the genetic control of SCT and the further development of molecular markers that are useful for breeding programs for the development of rice cultivars tolerant to cold stress. At the same time, rice accessions showing potential SCT will be integrated into the breeding program for varietal development.